COMPARISON OF AESTHETIC PERCEPTIONS OF THE BUCCAL CORRIDOR BETWEEN MALE AND FEMALE ADOLESCENTS (In Banjarmasin Non-urban Area) - Evaldo Stevan; Fajar Kusuma Dwi Kurniawan; Aulia Azizah; Irnamanda D.H; Riky Hamdani (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Smile aesthetics, particularly the buccal corridor, is a critical aspect of facial visual harmony that influences self-confidence and social interactions. Aesthetic perception is subjective and influenced by factors such as gender and demographic conditions. Objective: The study aimed to compare aesthetic perceptions of the buccal corridor between male and female adolescents attending senior high school in non-urban areas of Banjarmasin. Methods: An analytical observational study with a cross-sectional design was conducted, involving 216 respondents (108 males & 108 females) selected based on inclusion criteria. The instrument used to assess buccal corridor perception was a pictorial questionnaire featuring three buccal corridor variations (wide, moderate, and narrow), evaluated using a Visual Analog Scale (VAS). Data were analyzed with the Mann-Whitney test. Results: The results showed that female adolescents had the highest mean aesthetic perception score for the buccal corridor (mean: 62.99). Statistical testing revealed p < 0.05 for all categories, indicating a significant difference in aesthetic perception between males and females across all buccal corridor types. Conclusion: Female adolescents demonstrated higher aesthetic perception levels than males, suggesting they possess more selective and meticulous preferences when evaluating buccal corridor appearance.  Keywords: buccal corridor, smile aesthetics, perception, non-urban